Transanal Extrusion of the Ventriculoperitoneal Shunt Tube (Medicine Today, 2016)
Ventricular shunts are commonly employed in the management of hydrocephalus, Numerous complications such as dissection, migration and malfunction have been reported in the literature. Here we present a case of migration of the peritoneal catheter through anus who attended in our institute. He was managed successfully without further complications.Medicine Today 2015 Vol.27(2): 44-45